ASSESSMENT OF LOCALIZED KNOWLEDGE SPILLOVERS IN REGIONAL INNOVATION SYSTEMS - Novikova, Irina; Rudich, Slavko; Mukhoryanova, Oksana; Golubeva, Tatyana (Revista Inclusiones, 2020)
In the study, the authors prove that knowledge is the basis of any innovation system. Therefore, the determination of the mechanism for obtaining, accumulating and using knowledge can serve as the basis for the development of state policy aimed at creating and strengthening regional and national innovation systems. The authors propose a toolkit for identifying and evaluating methods, types and channels of knowledge spillovers and, using the example of a specific region, Stavropol Krai, show the results of using the developed toolkit.